Risk Factors for Type II Diabetes Mellitus in the Work Area of UPTD Public Health Center Lampaseh in 2020 - Tiara Aprilia; Rahmayani Rahmayani; Sri Rosita; Ismail Ismail; Diza Fathamira Hamzah (Universitas Serambi Mekkah, 2022)
Risk factors for type 2 diabetes mellitus that cannot be modified consist of age, family history of diabetes mellitus. While the risk factors for type 2 diabetes mellitus that can be modified include obesity, lack of physical activity, hypertension, dyslipidemia, unhealthy diet, smoking behavior. In addition, the wrong diet can cause type 2 diabetes such as consuming fast food, sweet foods, soft drinks. The purpose of this study was to determine the Risk Factors for Type II Diabetes Mellitus in the UPTD Work Area of the Lampaseh Health Center 2020. This study was analytic with a case control design. Population and sample amounted to 27 people. The study was conducted on January 4-16, 2021 and analyzed using odds ratios. The results showed that there was an effect of age (p value = 0.043, OR = 0.245), family history (p value = 0.019, OR = 5.339) and obesity (p value = 0.011, OR = 0.182) on the risk factors for type II Diabetes Mellitus in Indonesia. Working Area UPTD Lampaseh Health Center. It is recommended that health workers can provide counseling about type II diabetes mellitus (DM) to all DM patients, so that DM patients know about further treatment and can socialize to DM patients the risk if they have a family history. Keywords: Diabetes Mellitus, Obesity, Age, Family Story.